Etika Guru dalam Pemikiran Habib Sayyid Idrus Bin Salim Aljufri Studi Literatur Dalam Penerapan di pendidikan Alkhairaat - Gaus, Djulaiha (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2024)
The research method used in this research is a literature review, where the author completes all the readings related to the history of Sayyid Idrus' journey in establishing the madrasah to how Sayyid Idrus' ethics implemented the learning curriculum in the Alkhairaat madrasah. The results of the research show that to be an ideal educator you must first have a sense of